Usability of technological tools to overcome language barriers in health care: a scoping review protocol - Mike Mösko; Saskia Hanft-Robert; Annika Kreienbrinck (BMJ Open)
Introduction In many healthcare contexts globally, where the languages of care providers and patients do not match, miscommunication or non-communication can lead to inaccurate diagnoses and subpar treatment outcomes. In order to bridge these language barriers, a range of informal practices are used, such as family members or staff acting as interpreters, ‘receptive multilingualism’ or machine translation. The development and use of technological tools are increasing, but factors such as translation quality for complex health-related texts vary widely between languages. The objective of this scoping review is to (1) identify and describe the technological tools used in direct patient-provider communication to overcome a language barrier in a healthcare setting, (2) identify how the usability of these tools was evaluated and (3) assess the usability of the technological tools.Methods and analysis The scoping review will follow the Joanna Briggs Institute methodology. A search strategy using variations of the keywords ‘technological tools’, ‘language barrier’ and ‘healthcare’ will be applied in the following databases and research platforms: PubMed, PsycArticle, Scopus, EBSCOhost, ProQuest and Web of Science. All literature where individuals use a technological tool to overcome a language barrier in a healthcare context will be included and exported into the screening assistant software Rayyan. The search will be limited to articles written in German or English. Two independent reviewers will screen the articles, and all relevant extracted data will be presented in a descriptive summary.Ethics and dissemination This scoping review does not require ethical approval, as the study’s methodology consists of collecting data from publicly available sources. The findings will be disseminated through publication in an open-access, peer-reviewed journal and presentations at scientific conferences. The scoping review results will also guide future research in a multinational project investigating multilingualism in providing (mental) healthcare to migrants.